Pequenos compradores: o consumismo e a brincadeira na educação infantil - Angelo, Julia de Souza Delibero (2013)
In this work is analyzed how consumerism is present early in the school environment. From the perspective of the Critical Theory of the Society and taking some formulations developed within the sociology of childhood, especially about the need of investing the peculiarities which mark the children socialization and the role of them in relation to their forms of expression, investigation that way access to certain products, especially those considered "fashionable", changes the behavior of "small consumers" in day to day kindergarten, especially in times reserved for playing. The study began in 2012 with two joint steps: 1) interviews with 11 children 4-6 years old, enrolled in the same school, and 2) observations on-site (classroom, cafeteria and free areas). Already in 2013, in addition to data previously obtained, was conducted a focus group. The starting point of the study was to identify patterns of consumption and its interface with the games, focusing on the school environment. The questions took into account daily habits, bonds of friendship and consumer items such as food, toys and television attractions. Once traced the profile of this class, it was demonstrated that the consumption patterns of children respond to fads imposed by the cultural industry. No school context, this influence is particularly evident during the playing moments among students